Identity confirmation of anthocyanins in berries by LC–DAD–IM‐QTOFMS. Issue 4 (8th December 2020) - Delgado‐Povedano, María del Mar; de Villiers, André; Hann, Stephan; Causon, Tim
Abstract: Rugged analytical methods for the screening and identity confirmation of anthocyanins require a dedicated sample preparation, chromatographic setup, and the reliable generation of multiple identification points to confirm identity against the wide range of phenolic compounds typically present in food, beverage, and plant material samples. To this end, combinations of spectroscopic and mass spectrometric detection are frequently employed for this application to provide higher confidence in the absence of authentic standards. In the present work, low‐field drift tube ion mobility (DTIM) separation is evaluated for this task using a LC–DAD–DTIM–QTOFMS method. DTIM‐MS allows accurate determination of collision cross sections ( DT CCS ) for all analysed compounds as well as a precise alignment tool for reconciling fragment and precursor ions in data independent acquisition mode. The presented approach thereby allows for an anthocyanin screening method taking true advantage of all dimensions of the analytical platform: relative retention (RPLC), UV/VIS absorption spectrum, accurate mass, DT CCSN2, and confirmed high‐resolution fragment ions. From the analysis of authentic standards and several berry samples primarily from the Vaccinium genus, Level 1 confirmation data for six anthocyanins from the cyanidin family, and Level 2 confirmation for a further 29 anthocyanins confirmed in berry samples is provided. The method and accompanying dataset provided as part of this work provides a means to develop anthocyanin screening methods using the ion mobility dimension as an additional alignment and filtering parameter in data independent analysis acquisition across any LC–IM–MS platform.